Sistem Pengelolaan Keuangan Zakat Dikantor YBM PLN Unit Induk Daerah Sumatera Utara - Dini Setiana Saragih (STIKes Ibnu Sina Ajibarang, 2023)
North Sumatra Regional Main Unit Baitul Mal Foundation, which is part of a State-Owned Enterprise, Collects zakat funds collected from the income of PLN employees. This research aims to investigate the process of collecting and distributing zakat carried out by the North Sumatra Regional Main Unit State Electricity Company Baitul Maal Foundation. This research uses a qualitative approach with a case study design, data is collected through observation, interviews and documentation. The North Sumatra Regional Main Unit Baitul Mal Foundation is the object and source of research data. The research results show that zakat funds are obtained from employee salaries and processed by the amil before being distributed to mustahik in the form of vouchers.